Historicising 'Western Learned Magic': Preliminary Remarks - Otto, Bernd-Christian (Aries - Journal for the Study of Western Esotericism, 2016)
This programmatic paper conceptualises a research topic that has emerged in academic research over the past decades - 'Western learned magic' - and provides a theoretical foundation for its historicisation to come. Even though a large amount of specialised findings on this topic have been brought forward in recent years, a diachronic and cross-cultural overview of the history of 'Western learned magic' that reconstructs possible red threads through the manifold material is still an urgent desideratum. Based on the observation that most classic definitions and theories of 'magic' are irrelevant to the history of 'Western learned magic' - as these have been deduced from anthropological sources and theorising - this article raises a range of theoretical issues that need to be taken into account in the course of its historicisation: continuity, changeability, hybridity, deviance, morality, complexity, efficacy, and multiplicity. By means of this novel theoretical setup, historians will be able to work towards a methodologically sound history of 'Western learned magic' that takes into account the recent criticism against a second-order category of 'magic' while, at the same time, revealing out-dated stereotypes and master narratives on the topic.
Created from Fastlane, Scopus look-up
Keywords: discourse; dynamics; history; magic; ritual; Western Esotericism